A Power Allocation Strategy in Mobile Edge Computing for Maximizing Sum Secrecy Rate - Mao, Jiahui; Liao, Wensong; Tan, Chong; Liu, Hong; Zheng, Min (IEEE Vehicular Technology Conference, 2024)
This paper investigates the secure communication problem in the downlink of mobile edge computing (MEC) systems. A sum secrecy rate (SSR) maximization problem is formulated under transmission power and time constraints. To enhance the secrecy of the downlink transmission, we design the Geometric Water-Filling for SSR (GWF-SSR) algorithm for power allocation. Initially, we determine the minimum power allocation for each node to satisfy the transmission time constraint. Subsequently, the GWF-SSR algorithm is employed to allocate the remaining power. Numerical results demonstrate that the proposed algorithm outperforms existing benchmark algorithms. Besides, the GWF-SSR algorithm is superior to the Geometric Water-Filling (GWF) algorithm in terms of the SSR.